Non-communicable diseases, psychosocial wellbeing, and quality of life in Ga Mashie, Accra, Ghana: analysis from a community-based cross-sectional study - Kafui Adjaye-Gbewonyo; Irene Akwo Kretchy; Leonard Baatiema; Carlos S. Grijalva-Eternod; Olutobi Adekunle Sanuade; Samuel Amon; Hassan Haghparast-Bidgoli; Raphael Baffour Awuah; Swaib Abubaker Lule; Sedzro Kojo Mensah; Sandra Boatemaa Kushitor; Mawuli Komla Kushitor; et al. (BMC Public Health)
Abstract Background The burden of non-communicable diseases (NCDs), such as diabetes, hypertension, and obesity, is increasing globally, particularly in low- and middle-income countries. This has implications for physical, psychological and social aspects of health and wellbeing among individuals living with NCDs. This study sought to examine relationships between NCDs, quality of life (QoL) and psychosocial wellbeing in the urban community of Ga Mashie, Accra, Ghana. Methods A representative household survey was conducted among adults aged 25 years and over in Ga Mashie. Data were collected on self-reported NCD diagnoses and objectively measured random blood glucose, blood pressure and anthropometrics; sociodemographic characteristics; and health-related QoL and psychosocial wellbeing. Relationships between QoL, psychosocial wellbeing and diabetes, hypertension and obesity were examined using bivariate analyses and multivariable regressions comparing outcomes to those who did not have any of these conditions or any other self-reported NCD diagnosis. Results Data were gathered from 854 adults. Individuals with diabetes, hypertension and obesity had significantly reduced measures of QoL outcomes compared to those without these conditions or any other reported NCD. In particular, they were significantly less likely to report being satisfied or very satisfied with their health [Risk Ratios: 0.79 (95% CI: 0.63–0.98), 0.87 (95% CI: 0.79–0.95) and 0.87 (95% CI: 0.77–0.97) for diabetes, hypertension, and obesity, respectively]. They also had lower scores in the physical health domain of QoL compared to those with no known NCD [diabetes β -8.27 (95% CI: -13.55– -2.99); hypertension − 2.32 (95% CI: -4.84–0.21) and obesity − 2.74 (95% CI: -5.15– -0.32)]. Compared to the healthy comparison group, differences were more pronounced among those with a prior diagnosis of diabetes or hypertension than among those identified with raised blood glucose or raised blood pressure in our survey, but no prior diagnosis. Differences in indicators of psychosocial wellbeing such as social support, and psychological distress were not observed. Conclusion Diabetes, hypertension and obesity were associated with reduced QoL in Ga Mashie, Ghana. Further studies are needed to understand factors that influence health-related QoL among adults with NCDs, how these change over time, and to identify potential coping mechanisms that may influence this association.